Evaluation of diagnostic advances in Musculoskeletal Tuberculosis; the automated xpert MTB/RIF assay - Held, Michael (Division of Orthopaedic Surgery, 2019)
Background Xpert MTB/RIF (Xpert) is a rapid, automated, onsite nucleic acid amplification test for tuberculosis (TB). It is effective for the diagnosis of pulmonary TB but there is limited evidence for its usefulness in extrapulmonary TB, particularly musculoskeletal TB. Aims and hypothesis The aim of this thesis was to investigate the diagnostic accuracy of Xpert for musculoskeletal TB and for rifampicin resistance against a gold standard of culture or histology. Site of disease, HIV status, and age of patients, and accuracy in spinal compared to extraspinal TB were investigated as secondary objectives. The overarching hypothesis was that Xpert is more accurate and would provide results faster than the gold standard for musculoskeletal TB, and that it would have a higher yield in HIV infected patients, adult patients, and patients with spinal disease. Methods Prospective studies of patients with suspected musculoskeletal TB, at the tertiary care hospitals Groote Schuur and Red Cross Children’s Hospital in Cape Town, South Africa, were undertaken from June 2013 to March 2015. The diagnostic accuracy of Xpert was compared to culture or histopathology. Findings 206 biopsies of 201 patients older than 13 years of age (23% HIV positive) were analysed. The sensitivity and specificity of Xpert was 92.3% and 99.1% respectively. Xpert detected 8 cases more than culture (p = 0.069) and positive results were available 17 days earlier (<0.001). The sensitivity of Xpert in HIV positive patients was 96.9% (31/32) versus 89.6% (43/48) in HIV negative patients (p=0.225). The sensitivity of Xpert for spinal biopsies was 93.8% (95% CI 86.0-97.9) with specificity of 97.6% (95% CI 87.4 – 99.9), compared to extraspinal biopsies with a sensitivity of 81.8% (95% CI 48.2 – 99.7, p=0.164) and specificity of 100% (95% CI 95.1 – 100%, p=0.186). 109 osteoarticular samples of children 12 years of age or younger, with a median age of 5.6 years (IQR 2.2 – 8.7) were analysed. Xpert provided a sensitivity of 73.9% (95% CI 51.6-89.8) with a specificity of 100% (95% CI 95.7 - 100) and was available at a mean of 0.8 days (0.46- 1.4) compared to 21 days (19 – 30) for culture (p< 0.001). All rifampicin resistant cases were correctly diagnosed. A trend towards higher sensitivity in spinal tissue as well as HIV infected patients was observed. This study also provides evidence that Xpert has a lower sensitivity in children than in adults, yet, still detects more cases of paediatric musculoskeletal TB and is faster than culture. Histology was a useful test for the diagnosis of musculoskeletal TB, especially in children, and should be used alongside Xpert to provide the highest yield possible to detect TB. Conclusion: These first large studies on the accuracy of Xpert for musculoskeletal TB provide evidence for the usefulness of Xpert in the diagnosis of spinal TB, extraspinal TB, in HIV positive patients, and in childhood musculoskeletal TB. Based on these results, Xpert should be recommended as the initial test for diagnosis as it is more sensitive and faster than the gold standard of liquid culture.